Strengths and weaknesses of occupational safety and health's audit system in a manufacturing plant in Selangor - Kang, Eng Thye; Aljunid, Syed Mohamed; Rampal, Krishna Gopal (Department of Community Health, UKM, 2004)
Occupational Safety and Health Management System (OSHMS) has been introduced in many workplaces. Audit is also an integral component of an occupational safety and health system. A study was conducted to gain understanding of the weaknesses and strengths of OSH audit practice as perceived by three different target groups, namely safety and health officers (SHO), employer's representative (EMR) and employee's representative (EME). The research method involved an in-depth interview in a local Japanese Manufacturing Firm. Concerning the weaknesses of audit practice, SHOs indicated that operators were overloaded with too many audit activities and audit merely based on compliance to laws which are not enough. Whereas the employee representative felt the operator should be more involved in audit activities and audit findings were slow to reach the operators. Employer representative found that audits hardly changed the worker attitudes and auditors should not be fault finding and must work together with concern section in problem solving. Among the strengths of the audit system, SHOs commented that the written audit policy helped workers in better understanding of its purposes. Job rotation provided a good training for auditor to become competent. Employee representatives felt that it helped to raise safety awareness among operator and good feedback to them. Lastly,the employer representatives found that the audit practice helped to raise worker understanding on safety matters and auditors were able to notify the hidden safety problems that operator had difficulty to detect. In conclusion, from the preliminary study of a long good track record of OSH audit system in 2 Japanese manufacturing firm, it shows the general perception towards audit approach as the best approach to identify OSH weakness still receiving some contradict ideas from the various groups especially the EMR and EME as well. It implies that there is still room for improving the audit approach.